Higher exosomal tau, amyloid-beta 42 and IL-10 are associated with mild TBIs and chronic symptoms in military personnel. (19th September 2018) - Gill, Jessica; Mustapic, Maja; Diaz-Arrastia, Ramon; Lange, Rael; Gulyani, Seema; Diehl, Tom; Motamedi, Vida; Osier, Nicole; Stern, Robert A.; Kapogiannis, Dimitrios
ABSTRACT: Objective : Identify biomarkers in peripheral blood that relate to chronic post-concussive and behavioural symptoms following traumatic brain injuries (TBIs) to ultimately improve clinical management. Research design : We compared military personnel with mild TBIs (mTBIs) ( n  = 42) to those without TBIs ( n  = 22) in concentrations of tau, amyloid-beta (Aβ42) and cytokines (tumour necrosis factor alpha (TNFα, interleukin (IL)-6 and -10) in neuronal-derived exosomes from the peripheral blood. We utilized nanosight technology coupled with ultra-sensitivity immunoassay methods. We also examined the impact of post-concussive and behavioural symptoms including depression and post-traumatic stress disorder (PTSD) on these neuronal-derived markers. Results : We report that concentrations of exosomal tau ( F 1,  62  = 10.50), Aβ42 ( F 1,  61  = 5.32) and IL-10 ( F 1,  59  = 4.32) were elevated in the mTBI group compared to the controls. Within the mTBI group, regression models show that post-concussive symptoms were most related to exosomal tau elevations, whereas exosomal IL-10 levels were related to PTSD symptoms. Conclusions : These findings suggest that chronic post-concussive symptoms following an mTBI relate to altered exosomal activity, and that greater tau pathology may underlie chronic post-concussive symptoms that develop following mTBIs. It also suggests that central inflammatory activity contributes to PTSD symptoms following an mTBI, providing necessary insights into the role of inflammation in chronic PTSD symptoms.